Efektifitas Workshop Penulisan Publikasi Artikel Ilmiah bagi Peningkatan Kemampuan Guru Sekolah Dasar di Kabupaten Blora - Bening Sri Palupi (Manhaj: Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Writing the publication of scientific articles is one of the elements of the development of the teacher profession required by the Ministry of Education and Culture (2019). This gives the understanding that teachers are also required to be able to make their own scientific papers. This scientific article writing requires a deep understanding that is not enough systematic understanding but also the content of writing. The results of the survey conducted showed that most elementary school teacher participants did not understand the concept and way of publication of scientific articles. Therefore, there needs to be additional insight and experience for teachers related to this. The implementation of this activity is carried out through three stages, namely: (1) the preliminary stage; (2) the stage of implementation of the activity; and (3) the evaluation stage. Workshop activities aim to improve the willingness, understanding, and skills of teachers in the publication of scientific articles. Based on the results of the questionnaire showed that 90% of the teachers of workshop participants gave a positive impression related to the activities of the workshop.